EFFECT AZOTOBACTER, MYCORRHIZAE, VERMICOMPOST, AND NPK SPRAYING ON PRODUCTION OF CV HALAWANI GRAPES. - AL-Mamoori , Hussein.A.H.; JOODY, A.T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This experiment was carried out in one of the orchards of Diyala on grape vines, during two seasons 2022 - 2023, to study the effect of adding bacterial and fungal biofertilizers , vermicompost fertilizer, and foliar applied mineral fertilizer NPK on growth and production traits on cv. Halawani grape trees. The experiment was carried out a randomized complete block design within a split plot and three factors with three replicates, using 72 trees. The first factor included the addition of biofertilizers which included: without inoculation (M0), inoculation with 400 g of fungi (M1).Inoculation with 200 g of bacterial (M2) and inoculation with both bacteria and fungi (M3). The second factor included the addition of organic fertilizer with three treatments, without addition (N0), adding 5 kg/ tree-1 (N1) and adding 7 kg/tree-1 (N2), and the third factor included foliar applied mineral fertilizer NPK as two treatment, without spraying (F0) and Spraying with 2.5 ml L-1 of fertilizer (F1). Four foliar applications were applied at 30 day intervals when leaves reached full expansion. Results showed significant impact by the triple interaction treatment M3N2F1 on production traits represented by number of clusters in vine, cluster weight, total vine yield, 100 berries weight, and total sugar, by producing highest (49.16, 63.00 vine cluster-1, 761.3, 964.8 g, 37.41, 60.71 kg vine-1 , 568.20, 679.00 g, and19.24% ,17.72%), respectively for both seasons.